True bugs (Hemiptera-Heteroptera) of Botswana—Bibliographical inventory and new records - Krüger, Andreas; Deckert, Jürgen (Zootaxa, 2016)
The knowledge of insect biodiversity of Botswana is far from perfect. By 2015, there were only inventories publicly available for butterflies, dragonflies and grasshoppers. Here we report 331 species and subspecies of true bugs (Heteroptera), of which 242 records were extracted from scattered published literature and online sources, and 89 (27%) are new records for Botswana. These data significantly increase the number of insect species known from Botswana by roughly 30%.